Answer:
D
Explanation:
Expand (sinΘ + cosΘ)²
= sinΘ - cosΘ - (sin²Θ + 2 sinΘcosΘ + cos²Θ)
= sinΘ - cosΘ - sin²Θ - 2sinΘcosΘ - cos²Θ
= sinΘ - cosΘ - 2sinΘcosΘ - (sin²Θ + cos²Θ)
= - 2sinΘcosΘ - cosΘ + sinΘ - 1 → D
The trigonometric equation (sin Θ − cos Θ)^2 − (sin Θ + cos Θ)^3 can be simplified by:Using x for Θ: (sinx - cosx)^2 - (sinx + cosx)^2 = (sin^2 x - 2sinxcosx + cos^2 x) - (sin^2 x + 2sinxcosx + cos^2 x) = - 2 sinx cosx - 2 sinx cosx = - 4 sinx cosx = - 2sin(2x)
5.8m questions
7.5m answers